Pemberdayaan Masyarakat melalui Inovasi Paving Block dari Sampah Plastik di Desa Lohgung - Khoridatul Azizah; M. Syaifuddin; Ramanda Zakki Saputra; Moh Nasrul Amin (LP3M IAIFA Kediri, 2026)
The problem of plastic waste is also felt by the community of Lohgung Village, Brondong Subdistrict, Lamongan Regency, due to the limitations of the waste management system, which still largely relies on open burning and indiscriminate disposal. Through guidance, an innovative solution was introduced in the form of processing plastic waste into paving blocks based on community participation. This study employed the Participatory Action Research (PAR) method, combining literature review, field observations, and informal interviews. The implementation results demonstrated high community enthusiasm, reflected in their active participation in waste management seminars and hands-on practice in making paving blocks using recycled plastic, sand, oil, and cement. The resulting products possess sufficient durability for use in both household needs and the village’s light infrastructure. In addition to providing ecological benefits in the form of waste reduction, this activity also has the potential to create new economic opportunities through collaboration with the Village-Owned Enterprise (BUMDes) as an effort to ensure the program’s sustainability. Thus, the innovation of processing plastic waste into paving blocks has proven capable of addressing environmental issues while simultaneously enhancing the empowerment of the village community.